Modern Banking Law - Ellinger, E. P. (Eliahu Peter), 1933-; Lomnicka, Eva; Hooley, Richard (Oxford New York Oxford Univ Press (Sd), 2001)
The book examines the different types of banks and banking organizations operating in the United Kingdom, and reviews the new regulatory regime for banking under the financial services and markets act 2000. It provides analysis of the banker and customer relationship, explaining the different types of accounts available, the duties and liabilities of banks and the latest processes used in the clearance of cheques and money transfer.
Includes index.
nmn 11/06/13
Loans
Keywords: Banking Law